Athletes' perspectives on WADA and the code: a review and analysis. Issue 2 (3rd April 2019) - Gleaves, John; Christiansen, Ask Vest
ABSTRACT: This article presents athletes' perspective on the World Anti-Doping Agency (WADA) and the Code (WADC). Following a brief historical overview on athletes' view on doping controls, the article synthesizes existing empirical research on athletes' attitudes with examples and quotes expressed through various media on both anti-doping and specific topics within WADA's anti-doping framework. Although pockets of disconcert persist, the analysis shows that athletes generally express contentment with the current system and its ambitious aim to homogenise anti-doping efforts. However, athletes have also raised serious concerns on four specific issues, namely on a), the fair and consistent application of the rules for all athletes in a sport, b) the obligation to submit their whereabouts, c) the due processes when facing accusations of violations and d) the possibility for athletes to genuinely participate in the policy and decision making process. The chapter concludes with recommendations on how WADA could accommodate the athletes' concerns.